2021
DOI: 10.1186/s12884-021-03689-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying target behaviors for weight management interventions for women who are overweight during pregnancy and the postpartum period: a qualitative study informed by the Behaviour Change Wheel

Abstract: Background Maternal overweight is increasing, and it is associated with several risk factors for both the mother and child. Healthy lifestyle behaviors adopted during pregnancy are likely to impact women’s health positively after pregnancy. The study’s aim was to identify and describe weight management behaviors in terms of the Capability, Opportunity and Motivation Behaviour (COM-B) -model to target weight management interventions from both the perspectives of women who are overweight and mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Besides personal motivation, social motivation also had an influence on GWM behaviors. A study reported that maternity health professionals’ encouragement for pregnant women increased their GWM enthusiasm, and family support was very crucial [ 43 ]. Several studies highlighted the importance of motivational interventions for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Besides personal motivation, social motivation also had an influence on GWM behaviors. A study reported that maternity health professionals’ encouragement for pregnant women increased their GWM enthusiasm, and family support was very crucial [ 43 ]. Several studies highlighted the importance of motivational interventions for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…It is a matter of serious concern as it can impact various aspects of maternity care [ 16 ].The management of obesity is highly dependent on an individual’s willingness to bring about a behaviour change. This behaviour change depends on the knowledge, attitude and practices which is further guided by the source of information and socio-cultural myths and practices [ 17 ]. While exploring the knowledge, attitude, beliefs and perspectives of mothers regarding their weight status in the postpartum period, this study revealed certain noteworthy facts.…”
Section: Discussionmentioning
confidence: 99%
“…Step 2 : The analysis of performance, the target group and settings were examined through individual interviews with overweight women (n = 11) and focus group interviews with PHNs (n = 5) [ 28 ]. Weight management behaviors were identified from the perspective of the maternity care professionals and the overweight and obese women with the help of the Behaviour Change Wheel (BCW) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Step 3 : Development and selection of strategies and measures for practicing change were conducted by linking identified target behaviors and determinants of the national guidelines to the intervention components. Previously identified weight management target behaviors [ 28 ] were mapped to the matrix of BCW ( S1 Table ). These results were presented to the PHNs and based on their discussions and consensus the most helpful elements for their clinical work in maternity clinics were chosen.…”
Section: Methodsmentioning
confidence: 99%